Electrochemical oxidation of D-fructose solution using the Box–Behnken design methodology - Tay, Chen Lim; Fam, S.L. (Taylor & Francis Ltd., 2014)
The electrochemical oxidation of D-fructose solution was studied using a Box–Behnken design. Seventeen batch runs of electrochemical oxidation were conducted based on three sets of operating conditions generated using Design-Expert software. The effects of D-fructose concentration, applied voltage and NaOH concentration on oxidation percentage and oxidation rate were studied. As revealed by ANOVA, the D-fructose and NaOH concentrations significantly affected the oxidation percentage, and the applied voltage and NaOH concentration significantly affected the oxidation rate. Functional models for the oxidation percentage and oxidation rate were generated and reported. The electrochemical oxidation of D-fructose was optimised by maximising the D-fructose concentration and minimising the applied voltage and NaOH concentration. The models were validated by comparing the adjusted optimised solution with the experimental data. A 62.78% electrochemical oxidation percentage and an oxidation rate of 12.20 mM/L h were achieved using 82% D-fructose with 0.14 M NaOH and a 10 V applied voltage.